Efektivitas Implementasi Model Problem-based Learning Dalam Meningkatkan Literasi Sains Pada Materi Pencemaran Lingkungan Di SMA - Yoga Paratama Rukmananda; Suhartini (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of the Problem-based Learning (PBL) model on improving the scientific literacy of class X students of SMAN 1 Piyungan on environmental pollution material. The research method used is a quasi-experimental design with a non-equivalent control group design. This research was conducted at SMAN 1 Piyungan, even semester of the 2023/2024 academic year. The sample was class E1 as an experiment and class E2 as a control with the same number of students, namely 36 students. Data on students' scientific literacy abilities were obtained using multiple-choice questions. Analysis of the results of students' scientific literacy abilities was calculated using nonparametric statistics, namely the Mann Withney test. The PBL model is effective in improving students' scientific literacy abilities, as can be seen from the results of students' average scores or the results of the Mann Withney test. The average result of scientific literacy abilities in the experimental class was 77.20 with an N-Ggain value of 0.77, indicating that the increase was in the high category, while the average scientific literacy ability in the control class was 41.28 with an N-Ggain value of 0.41, indicating that the increase was in the moderate category. Based on the Mann Whitney test, the students' scientific literacy ability obtained a sig. (2-tailed) <0.05, meaning that there is a significant difference in students' scientific literacy ability between the control class and the experimental class. Based on the data analysis, it can be concluded that students' scientific literacy ability increases with the PBL model on environmental pollution material.